Immuno-Inflammatory Characteristics in Low Severity COVID-19 Patients with Digestive Symptoms - Caihan Duan; Shengyan Zhang; Jian Wang; Wei Qian; Chaoqun Han; Xiaohua Hou (Gastroenterology Research and Practice)
Aim. The outbreak of Coronavirus Disease 2019 (COVID-19) has resulted in a global pandemic, with the main manifestations being of respiratory nature, including pneumonia. It is noteworthy that digestive symptoms are also observed in COVID-19 patients. In this article, we describe the immuno-inflammatory characteristics of low severity COVID-19 patients with digestive symptoms. Methods. Patients with mild symptoms of COVID-19 were split into three groups based on the patients’ symptoms. The first group displayed digestive symptoms only, the second group displayed respiratory symptoms only, and the last group displayed both digestive and respiratory symptoms. Patients were discharged based on negative results of rRT-PCR testing for SARS-CoV-2 from at least two sequential respiratory tract specimens collected ≥24 hours apart. Multiorgan function and immuno-inflammatory characteristics were analyzed for all of the three groups. Results. Mild liver damage and activation of the immuno-inflammatory system were the most common abnormalities observed in patients with mild COVID-19 symptoms but no significant differences were found (P>0.05). Patients with digestive symptoms were more likely to have slightly higher and later peak values of inflammatory cytokines during the subsequent course of disease (P<0.05). In addition, a significant correlation between IL-2 and TNF level was found in the first group which included patients with digestive symptoms only (P<0.05). Conclusions. Patients with mild cases of COVID-19 only displaying digestive symptoms are a special subtype. Patients in this group were more likely to have slightly higher and delayed peak values of inflammatory cytokines during the subsequent course of the disease. Prevention and clinical management of this type should be taken into consideration.